2015
DOI: 10.3402/jchimp.v5.26069
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of vitamin D deficiency in the obese: a retrospective chart review

Abstract: ObjectiveTo determine whether the obese population is more likely to be vitamin D deficient compared to healthy and overweight individuals.Patients and methodsA retrospective chart review was performed for patients seen in two ambulatory clinics in South Florida over a 1-year period (n=402). Patients’ vitamin D levels drawn during annual wellness visits were analyzed. Subjects were categorized based on body mass index (BMI) as normal (BMI <24.9), overweight (BMI 25.0–29.9), and obese (BMI >30.0). Their 25-OH v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
(11 reference statements)
0
12
0
1
Order By: Relevance
“…Also, being fat‐soluble, more vitamin D may be sequestered in the abdominal fat, hence lowering circulating vitamin D . Vitamin D deficiency has been confirmed in obese subjects . In African–American overweight and obese subjects, supplementation with vitamin D (1,000, 2,000 and 4,000 IU) did not alter the body weight or the BMI in 6 months even though the plasma vitamin D was increased .…”
Section: Vitaminsmentioning
confidence: 99%
“…Also, being fat‐soluble, more vitamin D may be sequestered in the abdominal fat, hence lowering circulating vitamin D . Vitamin D deficiency has been confirmed in obese subjects . In African–American overweight and obese subjects, supplementation with vitamin D (1,000, 2,000 and 4,000 IU) did not alter the body weight or the BMI in 6 months even though the plasma vitamin D was increased .…”
Section: Vitaminsmentioning
confidence: 99%
“…reported a strong negative correlation between BMI and 25(OH)D level. Previous studies have reported that BMI declined when serum 25(OH)D levels were corrected from deficiency status . Interestingly, Vimaleswaran et al .…”
Section: Discussionmentioning
confidence: 97%
“…Probably, the active form of vitamin D decreases expression of pro-inflammatory cytokines such as IL-6, IL-1, and TNF-α involved in insulin resistance [149]. Some studies report a negative relationship between serum 25(OH) D levels, BMI [150][151][152], and HOMA-IR [147,152]. Maternal overweight and obesity are among the highest modifiable risk factors.…”
Section: Interaction Between Iron and Adipocytesmentioning
confidence: 99%